Kemampuan Penalaran Matematik dalam Pembelajaran Discovery Berbasis Mind Map pada Fungsi Kompleks - Retno Marsitin (Jurnal Tadris Matematika, 2018)
The purpose of this study is to describe mind-based discovery learning on complex functions to improve mathematical reasoning abilities. This study used a qualitative approach, with a classroom action research design, which was implemented in two cycles. The research was conducted at Universitas Kanjuruhan Malang with the subject of the study of mathematics education students who took complex functions with the number of 30 students. Data retrieval is: observation, test, documentation, field notes. Data analysis includes data reduction, data presentation, data review and conclusion drawing. Validity of data using triangulation. The results obtained from the data of academic ability, the ability of mathematical reasoning, the ability of student presentation and student response with better sesult. The conclusion of the research is mind map based discovery learning can improve the ability of mathematical reasoning and improve student academic success, so that learning is more qualified.